Laparoscopic real-time vessel navigation using indocyanine green fluorescence during the laparoscopic-Warshaw technique: First clinical experience - Ebihara, Yuma (J Minim Access Surg, 2021)
BACKGROUND: Laparoscopic-Warshaw technique (lap-WT) may be selected as a function-preserving operation for malignant border lesions in the tail region of the pancreas. However, previous reports showed that there are complications such as infection and abscess formation due to lack of blood flow to the spleen after surgery. To overcome the problems, we have performed real-time vessel navigation by using indocyanine green (ICG) fluorescence during lap-WT. MATERIALS AND METHODS: We report our experience of three patients with pancreatic tumour who underwent real-time vessel navigation during lap-WT at Hokkaido University from May 2017 to September 2018. RESULTS: The median operating time was 339 min (174–420). The median intraoperative bleeding was 150 ml (0–480). There were no incidences of complications. There were no cases with post-operative spleen ischaemia or abscess formation and varices formation. CONCLUSION: We believe that laparoscopic real-time vessel navigation using indocyanine green fluorescence during lap-WT could contribute in reducing the post-operative spleen-related complications.